Understanding Writing Habit in College: A Survey of Higher Education Students - Renggi Vrika (Universitas Hamzanwadi, 2023)
This research investigates the writing habits of students in higher education, employing a case study approach to attain a comprehensive understanding of these practices. The case study methodology is utilized to delve deeply into the intricate writing behaviors, motivations, and challenges faced by individual college students. Through a sample of 232 students from diverse faculties, insights are gathered via a meticulously designed survey that covers aspects such as writing frequency, time allocation, methodologies employed, and encountered difficulties. The findings underscore that, despite the diversity of academic disciplines, expected trends in writing habits emerge among students. While the initiation of writing may seem straightforward, challenges arise during the process, often leading to task-driven completion rather than the cultivation of consistent writing habits. The findings highlight the value of personalized interventions that identify the unique obstacles and motivations inherent in each field, allowing educators to fine-tune writing support programs. This research contributes to a nuanced understanding of writing practices in higher education, shedding light on students' attitudes toward writing. By acknowledging the diverse motivations and challenges faced, educators can strategically enhance writing support initiatives, fostering an environment where effective writing habits can flourish. The insights gleaned from this study not only inform academic discourse but also offer practical implications for educators seeking to empower students on their writing journey